Recurrent ventricular fibrillation: Experience with first responders prior to advanced life support interventions. (March 2015) - Telesz, Brian J.; Hess, Erik P.; Atkinson, Elizabeth; White, Roger D.
Abstract: Aim: Following defibrillation, ventricular fibrillation (VF) frequently recurs during out-of-hospital cardiac arrest (OHCA). Prior studies have reported conflicting results regarding its association with survival. The aim of this study was to examine the impact of recurrent VF in the presence of first responders before advanced life support (ALS) interventions. Methods: Electrocardiographic data from first responder automated external defibrillators (AEDs) were analyzed. A successful shock was defined as termination of VF for 5 s or longer. Recurrent VF was defined as any VF that occurred after a successful shock. The primary outcome was neurologically intact survival to hospital discharge (CPC 1–2). Results: 108 patients within our emergency system experienced a witnessed VF arrest. Of these, 73 (68%) had at least one recurrence of VF. Median time to recurrence of VF was 25 s [interquartile range (IQR) 11–66 s]. Median time in recurrent VF was 180 s (IQR 105–266 s). Survival was observed in 25 (71%) of patients with no recurrent VF and in 36 (49%) who had recurrence. Recurrent VF was associated with a lower odds of survival on univariate analysis (OR 0.39, 95% CI 0.16–0.92, p  = 0.0325). After adjusting for bystander CPR, gender and age, recurrent VF had a similar direction of effect but was no longer significantly associated with neurologically intact survival (OR 0.44, 95% CI 0.17–1.11, p  = 0.081). Conclusions: In the presence of first responders, VF recurred in 68% of patients. Recurrent VF was associated with a lower odds of survival, though its prognostic significance appeared to be blunted when considered in light of confounding variables. Recurrent VF may have significant survival implications, and further studies to assess its prognostic significance should be performed.